Besedilni sestavni deli - Škerget, Daniela (Organizacija znanja, 2023)
The purpose of this paper is to offer additional help to cataloguers for more uniform and higher quality cataloguing of textual component parts, and at the same time to gather information about where cataloguers can get informed about novelties and changes in the cataloguing of textual component parts. When cataloguing component parts, several standards are used together with the guidelines or recommendations of the ISBD(CP) (component parts). The selection of highlights was made on the basis of evaluations of 50 randomly selected records (twice a year), evaluations of test bases of candidates for obtaining the B1 license for mutual cataloguing of component parts, questions that cataloguers address to the National Bibliographic Center and the long-term experience of editors of records for component parts for Slovenian Bibliography.
Keywords: articles; besedilni sestavni deli; cataloguing; chapters in monographs; component parts; članki; katalogizacija; poglavja v monografskih publikacijah; sestavni deli; textual component parts